Not everything is as it seems: commentary on 'Stereophotogrammetric three‐dimensional photography is an accurate and precise planimetric method for the clinical visualization and quantification of human papilloma virus‐induced skin lesions'. (25th July 2019) - Skerlev, M.; Ljubojević Hadžavdić, S.; Sirotković‐Skerlev, M.
Abstract : Linked article : M. Rijsbergen et al . J Eur Acad Dermatol Venereol 2019;33 : 1506–1512.https://doi.org/10.1111/jdv.15474 .